PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Property, Real Estate dan Building Construction yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - Yulia Gea Sadasiha; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to empirically examine the effect of good corporate governance (institutional ownership, managerial ownership, independent board composition, audit committee composition, and the quality of audit) with leverage and firm size as a control variable to corporate performance (Tobin’s Q) in the property, real estate and building construction companies.  Sample of this research are property, real estate and building construction companies listed in the Indonesia Stock Exchange  from 2010 to 2012, which are 96 firms. Purposive sampling was used as sampling method. Data analysis method used was multiple regression analysis. Result of this research indicate that good corporate governance has a significant effect on firm performance with independent board composition. However, institutional ownership, managerial ownership, audit committee composition, and the quality of audit have no significant effect on firm performance (Tobin’s Q).